2006
DOI: 10.1085/jgp.200609576
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoinositide 3-Kinase Binds to TRPV1 and Mediates NGF-stimulated TRPV1 Trafficking to the Plasma Membrane

Abstract: Sensitization of the pain-transducing ion channel TRPV1 underlies thermal hyperalgesia by proalgesic agents such as nerve growth factor (NGF). The currently accepted model is that the NGF-mediated increase in TRPV1 function during hyperalgesia utilizes activation of phospholipase C (PLC) to cleave PIP2, proposed to tonically inhibit TRPV1. In this study, we tested the PLC model and found two lines of evidence that directly challenge its validity: (1) polylysine, a cationic phosphoinositide sequestering agent, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
383
4

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 348 publications
(416 citation statements)
references
References 48 publications
20
383
4
Order By: Relevance
“…Although PIP 2 and related phosphoinositides exert positive effects on the activity of many TRP channels, such as TRPV5 (32), TRPM4 (35,44), TRPM5 (45), TRPM7 (46,47), TRPM8 (33,34), and TRPC6 (7,48), it is inhibitory to few others, such as dTRPL (3) and TRPV1 (42, 49). Ironically, the inhibitory effect of PIP 2 on TRPV1 has been challenged by more recent studies showing the activating effect of PIP 2 on TRPV1 in inside-out patches (50,51). Therefore, among mammalian TRP channels, the PIP 2 -induced inhibition appears to be unique for TRPC4␣.…”
Section: Discussionmentioning
confidence: 99%
“…Although PIP 2 and related phosphoinositides exert positive effects on the activity of many TRP channels, such as TRPV5 (32), TRPM4 (35,44), TRPM5 (45), TRPM7 (46,47), TRPM8 (33,34), and TRPC6 (7,48), it is inhibitory to few others, such as dTRPL (3) and TRPV1 (42, 49). Ironically, the inhibitory effect of PIP 2 on TRPV1 has been challenged by more recent studies showing the activating effect of PIP 2 on TRPV1 in inside-out patches (50,51). Therefore, among mammalian TRP channels, the PIP 2 -induced inhibition appears to be unique for TRPC4␣.…”
Section: Discussionmentioning
confidence: 99%
“…25,26 TRPV channels are more controversial: although it is agreed that PI(4,5)P 2 plays an essential role in their modulation, whether PI(4,5)P 2 inhibits or activates TRPV1 is still an open question. [27][28][29][30] TRPV5 can be activated by PI(4,5)P 2 , and PI(4,5) P 2 seems to play a role in diminishing its physiological inhibition by Mg 2+ . 31 Modulation by the remaining mammalian TRP channels has not yet been reported, but it is likely that additional examples of lipid modulation will be identified.…”
Section: Lipids As Trp Channel Agonistsmentioning
confidence: 99%
“…PI(4,5)P 2 has been proposed to inhibit TRPV1, mediating the sensitizing actions of bradykinin and nerve growth factor (Chuang et al, 2001;Cao et al, 2013a). In contrast, others (including us) have proposed that PI(4,5)P 2 activates TRPV1 (Stein et al, 2006;Lukacs et al, 2007Lukacs et al, , 2013aKlein et al, 2008), and the depletion of PI(4,5)P 2 by phospholipase C may play a role in Ca 2+ -dependent desensitization (Mercado et al, 2010;Lukacs et al, 2013b). However, a recent study measured the apparent affinity of TRPV1 for diC8-PI(4,5)P 2 and found that the activating effects occurred with a K 1/2 of only 0.03 mol % in the plasma membrane, raising the question of whether PI(4,5)P 2 levels in the plasma membrane ever get sufficiently low selectivity must involve multiple, specific inter actions between TRPV1 and the phosphoinositide ligand.…”
Section: Discussionmentioning
confidence: 98%
“…The crystal structure of GIRK2 bound to PI(4,5)P 2 shows a structured binding pocket in which several hydrogen bonds are formed between basic residues in the protein and both the 4 and 5 phosphates (Whorton and MacKinnon, 2011). Based on this structure, it seems reasonable to predict that GIRK2 might display some phosphoinositide Mechanism for phosphoinositide selectivity and activation of TRPV1 ion channels the response of pain receptor neurons to noxious stimuli, disagreement about whether PI(4,5)P 2 activates or inhibits TRPV1 continues (Chuang et al, 2001;Prescott and Julius, 2003;Stein et al, 2006;Lukacs et al, 2007Lukacs et al, , 2013a; Ufret-Vincenty et al, 2011;Cao et al, 2013a,b;Senning et al, 2014). There is also disagreement about whether PI(4,5)P 2 interacts directly with TRPV1 or acts via the integral membrane protein Pirt (Kim et al, 2008;Ufret-Vincenty et al, 2011).…”
mentioning
confidence: 98%